Students Confidence in Increasing Learning Motivation - Eybarda Eybarda; Nurhayati Simatupang; Indra Kasih; Amir Supriadi (RIRAI Publisher, 2024)
The study shows that students' self-confidence in increasing learning motivation in physical education class VIII in participating in Physical Education learning at SMP Negeri 2 Harian in the 2023/2024 Academic Year is in the moderate category. This study was conducted at SMP Negeri 2 Harian with a total of 30 students consisting of 17 boys and 14 girls. The questionnaire items in this study were 30 statements prepared in Google Form https://forms.gle/w86uMf1yTbZntFnF6 . The data analysis technique used in this study is a quantitative descriptive analysis technique. The results of the study show that students' self-confidence in increasing learning motivation in physical education class VIII in participating in Physical Education learning at SMP Negeri 2 Harian in the 2023/2024 Academic Year is in the moderate category. The success of Physical Education learning must be supported by students who have self-confidence in participating in learning, and the results of this study state that the self-confidence of class VIII students of SMP Negeri 2 Harian in participating in Physical Education learning is in the moderate category, so teachers need to pay attention and try to improve the learning process that has been carried out, for example teaching methods that are in accordance with student interests, so that the level of student confidence increases in participating in Physical Education learning can be maintained, and even will increase.